Предмет: Алгебра,
автор: makc2k
помогите решить любой номер пожалуйста (лучше конечно всё)
Приложения:
Ответы
Автор ответа:
0
- limx-->4 [(4 - x) * (1 + √(5 - x))] / [(4 - x) * (3 + √(5 + x))] = Решение
2) limx-->4 (3 - √(5 + x))/(1 - √(5 - x)) =
limx-->4 [(3 - √(5 + x))*(3 + √(5 + x))*(1 + √(5 - ))]
/ [(1 - √(5 - x))*( 1 + √(5 - x))*(3 + √(5 + x)] =
limx-->4 = [3² - (√(5 + x))² *(1 + √(5 - x))] / [(1² - (√(5 - x))² * (3 + √(5 + x))] =
= limx-->4 [(9 -5 - x) * (1 + √(5 - x))] / [(1 - 5 + x) * (3 + √(5 + x))] =
= limx-->4 [(4 - x) * (1 + √(5 - x))] / [(-4 + x) * (3 + √(5 + x))] =
= - limx-->4 (1 + √(5 - x) / (3 + √(5 + x) = - (1 + √(5 - 4) / (3 + √(5 + 4) =
= - (1 + 1)/(3 + 3) = - 2/6 = - 1/3
2) limx-->4 (3 - √(5 + x))/(1 - √(5 - x)) =
limx-->4 [(3 - √(5 + x))*(3 + √(5 + x))*(1 + √(5 - ))]
/ [(1 - √(5 - x))*( 1 + √(5 - x))*(3 + √(5 + x)] =
limx-->4 = [3² - (√(5 + x))² *(1 + √(5 - x))] / [(1² - (√(5 - x))² * (3 + √(5 + x))] =
= limx-->4 [(9 -5 - x) * (1 + √(5 - x))] / [(1 - 5 + x) * (3 + √(5 + x))] =
= limx-->4 [(4 - x) * (1 + √(5 - x))] / [(-4 + x) * (3 + √(5 + x))] =
= - limx-->4 (1 + √(5 - x) / (3 + √(5 + x) = - (1 + √(5 - 4) / (3 + √(5 + 4) =
= - (1 + 1)/(3 + 3) = - 2/6 = - 1/3
Похожие вопросы
Предмет: Математика,
автор: saidamin1302
Предмет: Математика,
автор: gajvoronskaaaleksand
Предмет: Алгебра,
автор: yana2008156
Предмет: Биология,
автор: milochka01
Предмет: Обществознание,
автор: irina7429